2015
DOI: 10.1186/s12889-015-1810-6
|View full text |Cite
|
Sign up to set email alerts
|

Are associations between electronic media use and BMI different across levels of physical activity?

Abstract: BackgroundThe use of electronic media has been found to be a risk factor for higher BMI and for being overweight. Physical activity has been found to be associated with lower BMI and lower risk for being overweight. Little is known about whether the associations between physical activity and electronic media use are additive or interactive in predicting BMI and risk for overweight among adolescents.MethodsThe data used in this study stem from the 2009/2010 survey of “Health Behaviour in School-aged Children (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 57 publications
1
18
0
1
Order By: Relevance
“…Among girls, lower scores in self-esteem and general self-efficacy were associated with higher screen-based sedentary behaviours. Melkevik et al25 reported that the use of electronic media was associated with increased BMI z -scores and higher odds of being overweight in boys and girls who did not follow the physical activity guidelines. Recent research23 found a negative association between sedentary behaviour and engagement in sports in adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Among girls, lower scores in self-esteem and general self-efficacy were associated with higher screen-based sedentary behaviours. Melkevik et al25 reported that the use of electronic media was associated with increased BMI z -scores and higher odds of being overweight in boys and girls who did not follow the physical activity guidelines. Recent research23 found a negative association between sedentary behaviour and engagement in sports in adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…This result was contrary to previous studies where a significant longitudinal correspondence between time spent on media use and increased body fat was observed from childhood to adolescence ( 29 ). However, in cross-sectional studies, the results were somewhat mixed: some reported no evidence of a significant association between use of media and BMI ( 24 , 29 ), and others reported that media use appeared to be positively associated with BMI for girls only ( 29 , 30 ). Taken together, these inconsistent results further suggest the need for more prospective longitudinal studies to evaluate the effect of media use, timing of last food intake, sleep hours, and unhealthy eating behavior on BMI.…”
Section: Discussionmentioning
confidence: 99%
“…The few local studies that are available give some insight into the situation in only 9 counties out of 41. To this, data from studies performed abroad that included a Romanian cohort was included, but the exact geographical area of data collection is unclear in most cases [18,23,24,29]. Based on the information reviewed here, the prevalence of excess weight is in line with previous published data, namely 23.77% of children aged 2-19 have excess weight, 16.6% being overweight and 8.7% being obese (mean values based on WHO, CDC and IOTF derived prevalences, Table 4).…”
Section: Discussionmentioning
confidence: 99%